Copy number variation (CNV) of KIR genes characterized using qRT-PCR technique - Saltarrelli, Jerome; Willis, Dana; Rezvani, Katy; Cao, Kai (Human immunology, 2015)
Killer immunoglobulin-like receptors (KIR) are a group of cell surface proteins on the surface of natural killer cells. KIR genes are located in close proximity to one another in a head-to-tail fashion on chromosome 19. This arrangement permits misalignments or unequal crossover which can lead to deletions, duplicates or recombination. The non-reciprocal recombination increases the possibility of inequitable segregation of KIR genes leading to increased copies. The aim of the study was to develop assay for KIR CNV. We developed a KIR CNV assay for 2DL1, 2DL2, 2DL3, 2DS1, and 2DS2 by qRT-PCR (TaqMan® Copy Number Assay, Applied Biosystems) using primers and probes described by Jiang et al. (Genome research, 2012). Forty-three UCLA KIR exchange DNA and 14 members of 2 families with the present of these KIR were tested. Copy numbers were obtained using Life Technologies Copy Caller Software. Fig. 1 shows the CNV results of KIR2DL1 in 26 subjects. Of the 43 samples, majority showed 1 copy (63.0–84.6%) and some have 2 copies (12.5–29.6%) of all the 5 KIR genes. Three copies were observed only for KIR2DL1 in 7.4% of the subjects and 2DL3 in 3.8% of the subjects. None of the subjects has 4 copies in any of these KIR genes (Fig. 2). A member in 1 family carries 3 copies of KIR2DL1 with 2 copies in one haplotype and 1 copy in the second; another sibling bears a recombinant maternal haplotype (data not shown). KIR genes are polymorphic with a large number of allelic variants and also display copy number variations. One or 2 copies are more common than 3 or more copies. The immunological relevance of CNV in certain KIR genes has been revealed in virus infection such as resistance against human immunodeficiency virus or increased clearance of hepatitis C virus. KIR CNV may also have impact on stem cell transplant outcome. [Display omitted]